A Multimode Adaptive Pushover Procedure for Seismic Assessment of Integral Bridges - Ehsan Mohtashami; Ahmad Shooshtari (Advances in Civil Engineering)
This paper presents a new adaptive pushover procedure to account for the effect of higher modes in order to accurately estimate the seismic response of bridges. The effect of higher modes is considered by introducing a minimum value for the total effective modal mass. The proposed method employs enough number of modes to ensure that the defined total effective modal mass participates in all increments of the pushover loading. An adaptive demand curve is also developed for assessment of the seismic demand. The efficiency and robustness of the proposed method are demonstrated by conducting a parametric study. The analysis includes 18 four-span integral bridges with various heights of piers. The inelastic response history analysis is employed as reference solution in this study. Numerical results indicate excellent accuracy of the proposed method in assessment of the seismic response. For most bridges investigated in this study, the difference between the estimated response of the proposed method and the inelastic response history analysis is less than 25% for displacements and 10% for internal forces. This indicates a very good accuracy compared to available pushover procedures in the literature. The proposed method is therefore recommended to be applied to the seismic performance evaluation of integral bridges for engineering applications.